2017
DOI: 10.1038/s41598-017-01679-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Left Main Coronary Bifurcating Angle among Patients with Normal, Non-significantly and Significantly Stenosed Left Coronary Arteries

Abstract: We evaluated the correlation of the left main coronary bifurcating angle (LCBA) with the severity of coronary atherosclerosis, risk factors of coronary artery disease (CAD) and the feasibility of measuring the LBCA using the axial plane. Coronary Computed tomography angiographies (CTAs) of 313 patients between Nov. 2006 and Oct. 2013 were reviewed and separated into three groups. Group I (211 patients) had significant stenosis (≥50%) of the left anterior descending coronary artery (LAD) and/or left circumflex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 25 publications
(43 reference statements)
3
37
0
1
Order By: Relevance
“…The MPR view contains three perpendicular planes and corresponding 3D oblique plane that allows a radiologist to move in a precise manner and find the exact location of the bifurcation; while the manual rotation in VRT to find the best orthogonal view of the bifurcation angle via 'eye-balling' is a subjective decision by the radiologist. Further, Juan et al reported that 2D axial images are also reliable in measuring the left bifurcation angle when compared to invasive coronary angiography [24]. Their results support our findings of using 2D reconstructions for clinical measurements of bifurcation angles.…”
Section: B Clinical Measurementsupporting
confidence: 87%
See 1 more Smart Citation
“…The MPR view contains three perpendicular planes and corresponding 3D oblique plane that allows a radiologist to move in a precise manner and find the exact location of the bifurcation; while the manual rotation in VRT to find the best orthogonal view of the bifurcation angle via 'eye-balling' is a subjective decision by the radiologist. Further, Juan et al reported that 2D axial images are also reliable in measuring the left bifurcation angle when compared to invasive coronary angiography [24]. Their results support our findings of using 2D reconstructions for clinical measurements of bifurcation angles.…”
Section: B Clinical Measurementsupporting
confidence: 87%
“…Cui et al further confirmed the clinical value of using bifurcation angle for prediction of significant coronary stenosis [23]. Juan et al in their recent study reported the feasibility of using 2D axial images for measurement of left bifurcation angle [24]. However, accuracy of these measurement methods has not been fully determined.…”
Section: 'Introductionmentioning
confidence: 89%
“…Use of left coronary bifurcation angle as another criterion in diagnosing CAD has been increasingly reported in the literature with improved diagnostic accuracy when compared to conventional CCTA (16)(17)(18)(19)(20)(21). A cut-off value of 80° is recommended by these studies to decide the significance of coronary stenosis.…”
Section: A B C a B Cmentioning
confidence: 99%
“…Another approach to overcome this limitation is to measure the left coronary bifurcation angle and determine the significance of CAD. Diagnostic value of CCTA with use of left bifurcation angle has been shown in a number of studies with improved diagnostic performance reported when compared to the coronary lumen assessment (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Дана характеристика особенностям взаимоотношений артериального и венозного русел сердца [2,3]. однако работы, в которых представлены результаты сравнительного анализа ангиоархитектоники сердца в норме и при патологии, единичны [4,5].…”
unclassified